The contribution made by programme leadership consultants to the creation and maintenance of momentum for public service change programmes and the implications for their client sponsors: theory building within the context of a case study of the Maltese public service (1987-2001) - Mizzi, Konrad. (2011)
Consultants have diversified their offerings to include support for the formulation and implementation of complex public sector change programmes. Such programme leadership consultants provide mixed advisory-programme delivery support, which often translates into longer engagements. This growing phenomenon is less common and understood than the traditional view of consultants who act as advisors, and requires the focus of academia. The context of the research is a case study of the Maltese Public Service, wherein major change programmes were launched and sustained over a long timeframe. The case study spanned multiple legislatures and witnessed various changes in leadership and strategy. Interestingly Consultants were engaged throughout the case study in both an advisory and a programme leadership capacity, and contributed to the creation and maintenance of momentum for the change programmes, until the programmes eventually ran out of energy. These programmes were also confronted with resistance.